Video game addiction and psychological distress among expatriate adolescents in Saudi Arabia. (December 2017) - Saquib, Nazmus; Saquib, Juliann; Wahid, AbdulWaris; Ahmed, Abdulrahman Akmal; Dhuhayr, Hamad Emad; Zaghloul, Mohamed Saddik; Ewid, Mohammed; Al-Mazrou, Abdulrahman
Abstract: Introduction: Few studies have estimated screen time among Arab adolescents, and no studies, to date, have published data on addiction to video games or Internet games among Arab adolescents. This study aimed to assess the prevalence of addiction to video games and its correlation with mental health in a sample of expatriate high school students from the Al-Qassim region of Saudi Arabia. Methods: The survey was conducted in 2016 among 276 students enrolled in ninth through twelfth grades in the International Schools in Buraidah, Al-Qassim. Students who returned signed consent forms from their parents filled out a self-administered questionnaire that included validated scales on addiction to video games, general health, and lifestyle. Results: The proportion between the sexes and the schools were roughly equal. Around 32% were overweight or obese, 75% had screen time ≥ 2 h/day, and 20% slept < 5 h/night. Sixteen per cent (16%) were addicted to video games and 54% had psychological distress. Addiction to video games was strongly associated with psychological distress (OR = 4.1, 95% CI = 1.80, 9.47). Other significant correlates were female gender, higher screen time, and shorter sleep hours. Conclusions: The proportion of students with psychological distress was high. Future studies should investigate other potential correlates of distress such personal traits, family relations, and academic performance. Highlights: Proportion of adolescents addicted to video games was 16%. Relationship between video game addiction and psychological distress was significant. Risk factors for distress included being female, fewer hours of sleep, and higher screen time.